3D matrix promotes cell dedifferentiation into colorectal cancer stem cells via integrin/cytoskeleton/glycolysis signaling. Issue 11 (13th September 2022) - Han, Tong; Jiang, Yuhong; Wang, Xiaobo; Deng, Shuangya; Hu, Yongjun; Jin, Qianqian; Long, Dongju; Liu, Kuijie
Abstract: The potential for tumor occurrence triggered by cancer stem cells (CSCs) has emerged as a significant challenge for human colorectal cancer therapy. However, the underlying mechanism of CSC development remains controversial. Our study provided evidence that the bulk of tumor cells could dedifferentiate to CSCs and reacquire CSC‐like phenotypes if cultured in the presence of extracellular matrix reagents, such as Matrigel and fibrin gels. In these 3D gels, CD133 − colorectal cancer cells can regain tumorigenic potential and stem‐like phenotypes. Mechanistically, the 3D extracellular matrix could mediate cytoskeletal F‐actin bundling through biomechanical force associated receptors integrin β1 (ITGB1), contributing to the release of E3 ligase tripartite motif protein 11 (TRIM11) from cytoskeleton and degradation of the glycolytic rate‐limiting enzyme phosphofructokinase (PFK). Consequently, PFK inhibition resulted in enhanced glycolysis and upregulation of hypoxia‐inducible factor 1 (HIF1α), thereby promoting the reprogramming of stem cell transcription factors and facilitating tumor progression in patients. This study provided novel insights into the role of the extracellular matrix in the regulation of CSC dedifferentiation in a cytoskeleton/glycolysis‐dependent manner. Abstract : F‐actin bundling was modulated by the extracellular matrix through biomechanical forces via the receptor integrin β1, contributing to the release of E3 ligase Tripartite motif protein 11 (TRIM11) from the cytoskeleton and to the degradation of the glycolytic rate‐limiting enzyme phosphofructokinase (PFK). Inhibiting PFK contributed to enhanced glycolysis and upregulation of hypoxia‐inducible factor 1 (HIF1α), thereby reprogramming stem cell transcription factors and facilitating the dedifferentiation of colorectal cancer cells.